Day 3 - 1200 - Frederick Paquet.pdf - Gill, Philip (Cranfield University, 2023)
Effect of the flame structure on nitrocellulose-based materials deflagration properties Frederick Paquet - Frederick Paquet Scientific Consulting Mario Paquet - GD-OTS Canada 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'